2019
DOI: 10.1177/1073274819863802
|View full text |Cite
|
Sign up to set email alerts
|

Cancers in Vietnam—Burden and Control Efforts: A Narrative Scoping Review

Abstract: Although the burden of cancer is rapidly growing in Vietnam, there was no up-to-date review that describes cancer burden and control in Vietnam throughout the literature. By identifying various risk factors, means of prevention, and methods for early detection, this review seeks to systematically summarize the evidence for the future planning and management of cancer occurrence in Vietnam. Additionally, this report aims to identify improvements which are necessary for the treatment and palliative care of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 63 publications
(116 reference statements)
0
80
0
3
Order By: Relevance
“…This study investigates the previously unexamined experience of women with breast cancer in Vietnam along different points of the diagnostic and treatment pathway. Data on cancer are limited with cancer registries being hospital based and datasets being partly based on mathematical models 1. Previous studies have, however, indicated increased challenges for Vietnamese society and the health system posed by non-communicable diseases, and particularly breast cancer given that it often is diagnosed in later stages 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the previously unexamined experience of women with breast cancer in Vietnam along different points of the diagnostic and treatment pathway. Data on cancer are limited with cancer registries being hospital based and datasets being partly based on mathematical models 1. Previous studies have, however, indicated increased challenges for Vietnamese society and the health system posed by non-communicable diseases, and particularly breast cancer given that it often is diagnosed in later stages 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…Vietnam displays higher incidence rate of lung cancer than the average worldwide incidence (14.5% versus 11% of all new cases) despite having the same level of mortality rate according to the latest Globocan data 18,19 . Also, in Vietnam lung cancer is the most aggressive type of cancer in men and ranks as the second leading cause of cancer deaths in women 18,19 . Therefore, it is important to assess the mutation landscape as well as their association with unique clinicopathological features of Vietnamese NSCLC patients.…”
mentioning
confidence: 97%
“…A question raised by this media content analysis concerns the disconnection between information shared in the media regarding breast cancer risk factors, symptoms and expectations for treatment, and reported knowledge by women in other studies. Despite the largely factual and accurate reporting about breast cancer in the mass media, knowledge and awareness about breast cancer is generally poor [4,[28][29][30]. This raises questions about the medium, focus, and delivery of content.…”
Section: Discussionmentioning
confidence: 99%